Guerbet glycolipids from mannose: liquid crystals properties - Patrick, Melonney; Zahid, Noor Idayu Mat; Kriechbaum, Manfred; Hashim, Rauzah (Taylor & Francis, 2018)
Using mannose as the sugar head, five Guerbet glycolipids with chain ranges from C 8 to C 24 were synthesised and studied for their liquid crystal behaviour. Differential scanning calorimetry, optical polarising microscopy and small-angle X-ray scattering were employed to determine the thermal, phase and structure properties. Unlike monoalkylated glycolipids, these Guerbet mannosides showed a glass transition below 0°C, except for α-Man-OC 14 C 10 . In the dry state, lamellar was observed for α-Man-OC 6 C 2 and α-Man-OC 8 C 4 , while α-Man-OC 12 C 8 and α-Man-OC 14 C 10 formed non-lamellar phases, including inverse bicontinuous cubic phase of space group Ia3d and inverse hexagonal phase, respectively. The phase for middle-chain mannoside (α-Man-OC 10 C 6 ) could not be assigned conclusively at room temperature, but this metastable phase forms lamellar above 37°C. The partial binary phase diagrams in water were also determined. Under excess water conditions at room and physiological temperatures, these materials form normal micellar solution, lamellar, inverse bicontinuous cubic of space group Pn3m and inverse hexagonal phases. The results were compared with those from other monosaccharide glycolipids from the same sugar Guerbet family. Although these compounds are obvious candidate material for lyotropic applications such as drug carrier and protein crystallisation medium, possible thermotropic application is now being explored.